Population data for 12 X-STRs loci in Malaysian Malay and Chinese populations - Aedrianee Reeza Alwi; Naji Arafat Mahat; Faezah Mohd Salleh; Seri Mirianti Ishar; Mohammad Rahim Kamaluddin; Mohd Radzniwan A Rashid; Sharifah Nany Rahayu Karmilla Syed Hassan; Sasitaran Iyavoo (Elsevier Ltd, 2024)
Indexed by Scopus